MicroRNAs: Important Regulators of Induced Pluripotent Stem Cell Generation and Differentiation - Zeng, Zhao-Lin; Lin, Xiao-Long; Tan, Li-Lan; Liu, Ya-Mi; Qu, Kai; Wang, Zuo (Stem cell reviews and reports, 2018)
Induced pluripotent stem (iPS) cells can differentiate into nearly all types of cells. In contrast to embryonic stem cells, iPS cells are not subject to immune rejection because they are derived from a patient's own cells without ethical concerns. These cells can be used in regenerative medical techniques, stem cell therapy, disease modelling and drug discovery investigations. However, this application faces many challenges, such as low efficiency, slow generation time, partially reprogrammed colonies and tumourigenicity. Numerous techniques have been formulated in the past decade to improve reprogramming efficiency and safety, including the use of different transcription factors, small molecule compounds and non-coding RNAs. Recently, microRNAs (miRNAs) were found to promote the generation and differentiation of iPS cells. The miRNAs can more effectively and safely generate iPS cells than transcription factors. This process ultimately leads to the development of iPSC-based therapeutics for future clinical applications. In this comprehensive review, we summarise advances in research and the application of iPS cells, as well as recent progress in the use of miRNAs for iPS cell generation and differentiation. We examine possible clinical applications, especially in cardiology.